Stigmatizing Images in Obesity Health Campaign Messages and Healthy Behavioral Intentions. (August 2016) - Young, Rachel; Subramanian, Roma; Hinnant, Amanda
Background . Antiobesity campaigns blaming individual behaviors for obesity have sparked concern that an emphasis on individual behavior may lead to stigmatization of overweight or obese people. Past studies have shown that perpetuating stigma is not effective for influencing behavior. Purpose . This study examined whether stigmatizing or nonstigmatizing images and text in antiobesity advertisements led to differences in health-related behavioral intentions. Method . Participants in this experiment were 161 American adults. Measures included self-reported body mass index, weight satisfaction, antifat attitudes, and intention to increase healthy behaviors. Results . Images in particular prompted intention to increase healthy behavior, but only among participants who were not overweight or obese. Conclusion . Images and text emphasizing individual responsibility for obesity may influence behavioral intention among those who are not overweight, but they do not seem to be effective at altering behavioral intentions among overweight people, the target audience for many antiobesity messages. Images in antiobesity messages intended to alter behavior are influential and should be selected carefully.